Cerebral autoregulation in the operating room and intensive care unit after cardiac surgery. (May 2021) - Nakano, Mitsunori; Nomura, Yohei; Whitman, Glenn; Sussman, Marc; Schena, Stefano; Kilic, Ahmet; Choi, Chun W.; Akiyoshi, Kei; Neufeld, Karin J.; Lawton, Jennifer; Colantuoni, Elizabeth; Yamaguchi, Atsushi; et al.
Abstract: Background: Cerebral autoregulation monitoring is a proposed method to monitor perfusion during cardiac surgery. However, limited data exist from the ICU as prior studies have focused on intraoperative measurements. Our objective was to characterise cerebral autoregulation during surgery and early ICU care, and as a secondary analysis to explore associations with delirium. Methods: In patients undergoing cardiac surgery ( n =134), cerebral oximetry values and arterial BP were monitored and recorded until the morning after surgery. A moving Pearson's correlation coefficient between mean arterial proessure (MAP) and near-infrared spectroscopy signals generated the cerebral oximetry index (COx). Three metrics were derived: (1) globally impaired autoregulation, (2) MAP time and duration outside limits of autoregulation (MAP dose), and (3) average COx. Delirium was assessed using the 3-Minute Diagnostic Interview for CAM-defined Delirium (3D-CAM) and the Confusion Assessment Method for the ICU (CAM-ICU). Autoregulation metrics were compared using χ 2 and rank-sum tests, and associations with delirium were estimated using regression models, adjusted for age, bypass time, and logEuroSCORE. Results: The prevalence of globally impaired autoregulation was higher in the operating room vs ICU (40% vs 13%, P <0.001). The MAP dose outside limits of autoregulation was similar in the operating room and ICU (median 16.9 mm Hg×h; inter-quartile range [IQR] 10.1–38.8 vs 16.9 mm Hg×h; IQR 5.4–35.1, P =0.20). In exploratory adjusted analyses, globally impaired autoregulation in the ICU, but not the operating room, was associated with delirium. The MAP dose outside limits of autoregulation in the operating room and ICU was also associated with delirium. Conclusions: Metrics of cerebral autoregulation are altered in the ICU, and may be clinically relevant with respect to delirium. Further studies are needed to investigate these findings and determine possible benefits of autoregulation-based MAP targeting in the ICU.